2009
DOI: 10.14411/eje.2009.021
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and speciation in the dragonfly Sympetrum striolatum/nigrescens (Odonata: Libellulidae): An analysis using AFLP markers

Abstract: Abstract. There has been a long-standing debate as to whether Sympetrum striolatum (Charpentier, 1840) and the darker northern form, S. nigrescens (Lucas, 1912) should be recognised as separate species of dragonfly. Here we address this question using genetic analysis based on AFLP markers and samples collected from sites across the species' United Kingdom range. The program STRUC-TURE finds no support for specific status. Instead, it reveals strong patterns of divergence between populations sampled from Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In many cases, molecular results have supported classical morphological work, but there are cases where unexpected novelty emerges (Parkes et al, 2009).…”
Section: Discussionmentioning
confidence: 78%
“…In many cases, molecular results have supported classical morphological work, but there are cases where unexpected novelty emerges (Parkes et al, 2009).…”
Section: Discussionmentioning
confidence: 78%
“…Sympetrum striolatum (Libellulidae) S. striolatum is a palearctic dragonfly [28] that is found in Europe and other areas in the Mediterranean [29], with bodies of salt-water likely serving as a major barrier to gene flow within this species [30]. A demographic model of S. striolatum, generated from a reference assembly of an individual from Wytham Woods, Oxfordshire, UK [31] estimated a relative stable effective population size around 1 million individuals throughout most of the past 10 million years (which may predate the divergence times of this species), with declines to an effective population size of around 100,000 occurring in the last 100,000 years [32].…”
Section: Pachydiplax Longipennis (Libellulidae)mentioning
confidence: 99%
“…It has been historically observed in southern Europe and the Mediterranean (Borkenstein & Jödicke, 2022). An analysis of amplified fragment length polymorphism (ALFP) markers comparing genetic signatures from different individuals concluded that salt water barriers inhibit intra-species breeding within S. striolatum populations, leading to decreased genetic diversity (Parkes et al, 2009). This finding raised concerns regarding rising sea levels that could represent barriers to gene flow of this species.…”
Section: Sympetrum Striolatummentioning
confidence: 99%